Effective utilization of iron ore slime, a mining waste as adsorbent for removal of Pb(II) and Hg(II). Issue 1 (February 2017) - Sarkar, Santanu; Sarkar, Supriya; Biswas, Pinakpani
Abstract: The environmental pollution is rapidly increasing due to industrialisation. Among all toxic pollutants, heavy metal ions easily bio-accumulate in living organism and such type of accumulation causes detrimental effects in the whole life cycle of all living inhabitants. Protection of the environment for its sustainable development has led to several initiatives been taken for wastewater treatment. In this regard, the present study represents commercially feasible technique for the complete removal of lead and mercury ions from industrial wastewater, by using naturally occurring iron ore slime. It has been observed that Pb(II) and Hg(II) ions can be removed efficiently within a long range of pH. The present study also includes the effect of several process parameters in adsorption of heavy metals such as initial concentration of pollutants and adsorbent, pH and retention time. Adsorption was carried out via both mixing-settling and packed column methods and also adsorption isotherm was investigated here. The results of the characterisation study of slime ensure that the major component is hematite and moreover, high surface area is the influencing parameters for adsorption of heavy metals.